PERAN KELEMBAGAAN ADAT KENEGERIAN SENTAJO DALAM PENGELOLAAN HUTAN LINDUNG KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Ahsanur Rizqi; Zulfan Saam; Suardi Tarumun (Program Pascasarjana Universitas Riau, 2018)
The Kuantan Singingi community has wisdom in maintaining the environment such as forests, rivers, lakes and slope hills. One of them is the Kuantan Singingi Sentajo Forest that is one of the protected forests. This research was carried out for one month in May 2018 in Sentajo Protection Forest, Sentajo Raya District, Kuantan Singingi Regency. The method that used in this study was a case study method with a qualitative approach. Data collection uses interviews and observations. The results showed that Sentajo Protection Forest is a type of tropical rain forest with high biodiversity. The values and norms of the Kenegerian Sentajo Protected Forest can be seen from ecological, social and economic values. The ecological values are still preserved by flora and fauna, maintaining the preservation of the Kenegerian Sentajo Protection Forest has a strong rooted value applies to the understanding of the existence of the founding fathers of Kampung. Sentajo in protection Forest in Sentajo. Social values can be seen from the preservation of the track runway that is a cultural tradition that has been going on from the colonial era to the present by utilizing wood from protected forests and the community working together to make traditional houses under the leadership of Datuk Penghulu 4 (four) tribes. The economic value contained in protected forests is closely related to the daily needs of communities around protected forests such as community ponds and rice fields whose water comes from protected forests. The role of institutions carried out in the management of Sentajo Protection Forest resources such as taking of decisions regarding resource management forest power. Give permission regarding the use of forest resources. Establishment of UPT KPHL offices, information boards and prohibition boards. Community empowerment and safeguarding forest areas are carried out directly or indirectly.